Spatio-Temporal Variation in Water Quality of Selected Lakes in Eastern Dry Agro Climatic Zone of Karnataka State, India - Murthy, Tanaya S; K L , Prakash (International Journal of Ecology and Environmental Sciences, 2024)
Monitoring water quality is a helpful tool for assessing the effects of pollution sources, ensuring effective management of water resources, and preserving aquatic life in surface water bodies. Hence, the present study focussed on evaluating the water quality of thirty-four selected lakes in Chikkaballapura taluk by characterizing physico-chemical parameters, Dissolved oxygen levels, organic loads (viz., BOD and COD) and WQI. The TDS level in the study area was well within the tolerance limit of 1500 mg/L, illustrating medium salinity (viz., electrical conductivity) in lake water. None of the lakes in the study area recorded nitrate concentrations above the tolerance limit of 50 mg/L during either season. Kolavanahalli and Varamallenahalli lakes witnessed nitrate levels of over 40 mg/L, while the pooled mean phosphate concentration was 0.40 mg/L during the study periods. High organic load in terms of COD was witnessed in selected lakes, as revealed by their ranges 64.0-144.0 mg/L (mean: 98.6 mg/L) and 60.8-136.0 mg/L (mean: 91.7 mg/L), respectively, during the pre- and post-monsoon seasons. Despite organic load, dissolved oxygen concentration ranged from 4.45-6.10 mg/L and 4.25-5.88 mg/L during these seasons, well above the desirable 4.0 mg/L limit. The present study also demonstrated the contribution of phosphate and nitrates towards organic loadings (viz., BOD and COD), illustrating increased anthropogenic contribution like entry of raw sewage, agricultural runoff, and others. Irrigation suitability was observed for most lakes, as revealed by their SAR, percent sodium and RSC values.